Associations Between Perinatal Dioxin Exposure and Circadian Clock Gene mRNA Expression in Children in Dioxin-Contaminated Areas of Vietnam - Thao Ngoc Pham; Hoa Thi Vu; Takafumi Tasaki; Tai Pham-The; Nghi Ngoc Tran; Muneko Nishijo; Tien Viet Tran; Hai Anh Tran; Tomoya Takiguchi; Yoshikazu Nishino (Toxics)
We investigated the impact of perinatal dioxin exposure (indicated by dioxin levels in maternal breast milk) on clock gene mRNA expression in buccal cells of 9-year-old children from the Da Nang birth cohort in Vietnam using reverse transcription polymerase chain reaction. Of the 56 boys and 34 girls (67% detection rate) in whom PER1 was detected, BMAL1 was detected in only 16 boys and 15 girls. Dioxin levels were significantly higher in girls with BMAL1 detection than in girls without detection. In girls, higher relative BMAL1 expression levels were associated with greater levels of 2,3,7,8-tetrachlorodibenzo-p-dioxin and toxic equivalents of polychlorinated dibenzodioxins and polychlorinated dibenzofurans. Moreover, BMAL1 expression levels were correlated with shorter night sleep duration on weekdays, greater sleep duration on holidays, and higher hyperactivity scores. After adjusting for maternal parity, relative PER1 expression levels were higher in boys with higher toxic equivalents of polychlorinated dibenzofuran than those in girls. Although higher PER1 expression levels were correlated with greater verbal aggression and hostility scores in girls, no such associations were found in boys. These findings suggest the possible existence of sex-specific effects of perinatal dioxin exposure on circadian rhythms regulated by clock genes, particularly BMAL1, leading to sleep and behavioral problems in later life.